2011
DOI: 10.3109/10253890.2011.624224
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing effects of acute psychosocial stress on priming of non-declarative memory in healthy young adults

Abstract: Social stress affects cognitive processes in general, and memory performance in particular. However, the direction of these effects has not been clearly established, as it depends on several factors. Our aim was to determine the impact of the hypothalamus-pituitary-adrenal (HPA) axis and sympathetic nervous system (SNS) reactivity to psychosocial stress on short-term non-declarative memory and declarative memory performance. Fifty-two young participants (18 men, 34 women) were subjected to the Trier Social Str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 49 publications
(76 reference statements)
2
22
1
1
Order By: Relevance
“…Similar to previous studies in young and older people, in the stress group, women showed a lower cortisol response than men Hidalgo et al, 2012;Kudielka, Buske-Kirschbaum, Hellhammer, & Kirschbaum, 2004). Thus, it is possible that the lack of stress effect on memory retrieval observed in women may be due to this low cortisol reactivity.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar to previous studies in young and older people, in the stress group, women showed a lower cortisol response than men Hidalgo et al, 2012;Kudielka, Buske-Kirschbaum, Hellhammer, & Kirschbaum, 2004). Thus, it is possible that the lack of stress effect on memory retrieval observed in women may be due to this low cortisol reactivity.…”
Section: Discussionsupporting
confidence: 87%
“…Participants in the stress group were exposed to the Trier Social Stress Test (TSST; Kirschbaum, Pirke, & Hellhammer, 1993; for a detail description of the TSST see: Almela, Hidalgo, Villada, van der Meij, et al, 2011), and participants in the control group performed a control task that consisted of 5 min of talking aloud about a recent non-emotional experience, and 5 min counting by 5 aloud. This kind of control task has been used in previous studies (Almela, Hidalgo, Villada, van der Meij, et al, 2011;Hidalgo et al, 2012), and it was designed to be similar to the stress task in mental workload and global physical activity, but without a stressful component. After the stress/control task, participants answered four questions (5-point Likert scale; not at all = 1, to extremely = 5) about their perceptions of both tasks (situational appraisal), based on the following aspects: stress, difficulty, frustration and effort (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Through ascending projections from brainstem nuclei where the locus coeruleus norepinephrine and midbrain dopaminergic systems locate, these stress-sensitive catecholamines alter neuronal functioning of widely distributed brain regions, particularly including the PFC (Arnsten and Li, 2005; Aston-Jones and Cohen, 2005; Arnsten, 2009; Sara, 2009). Converging evidence from human behavioral and neuroimaging studies have confirmed that acute stress indeed alters WM performance with both detrimental (Elzinga and Roelofs, 2005; Oei et al, 2006; Luethi et al, 2008; Schoofs et al, 2008) and enhancing (Lewis et al, 2008; Weerda et al, 2010; Hidalgo et al, 2011) effects, likely through altered efficiency of WM-related processing in dorsolateral PFC (Porcelli et al, 2008; Qin et al, 2009; Weerda et al, 2010). Interestingly, animal studies suggest that stress-sensitive catecholamines exert an inverted U-shaped influence on prefrontal functions (Aston-Jones and Cohen, 2005; Vijayraghavan et al, 2007), in which prefrontal functioning reaches an optimum at an intermediate level of catecholaminergic activity (Arnsten and Li, 2005; Aston-Jones and Cohen, 2005; Vijayraghavan et al, 2007).…”
Section: Introductionmentioning
confidence: 97%
“…There are only a few studies investigating the effects of cortisol on implicit memory processes and these showed mixed results [36], [37], [38], [39]. However, as described above, intrusions are thought to rely on implicit memory processes, e.g.…”
Section: Introductionmentioning
confidence: 99%